Tomato phyE Is Required for Shade Avoidance in the Absence of phyB1 and phyB2 - Schrager-Lavelle, Amanda; Herrera, Leslie A.; Maloof, Julin N. (Frontiers in Plant Science, 2016)
The phytochrome (phy) family of red and far-red photoreceptors provides plants with critical information about their surrounding environment and can signal downstream developmental and physiological changes. Neighboring plants compete for limited light resources, and their presence is detected by the phytochrome photoreceptors as a reduced ratio of red: far-red light. One common response to shade is increased elongation of petioles and internodes to compete with their neighbors. While the phytochrome family, phyB in particular, has been well studied in Arabidopsis, information about the other phytochrome family members is limited, especially in sympodial crop plants such as tomato, that have a very different architecture from that of the model plant. To study the tomato phytochrome family we took advantage of several existing mutants and generated an artificial miRNA (amiRNA) line to target SlPHYE, the remaining phytochrome B subfamily member with no currently available mutant line. Here, we characterize internode elongation and shade avoidance phenotypes of the SlPHYE amiRNA line (PHYE amiRNA) In addition, higher order phytochrome subfamily B mutants were generated with the PHYE amiRNA line to investigate the role of SlphyE within the phyB subfamily. We find that the PHYE amiRNA line has no detectable phenotype on its own, however in higher order combinations with SlphyB1 and/or SlphyB2 there are notable defects in shade avoidance. Most notably, we find that the triple mutant combination of SlPHYE amiRNA, SlphyB1, and SlphyB2 has a phenotype that is much stronger than the SlphyB1 SlphyB2 double, showing constitutive shade avoidance and little to no response to shade. This indicates that SlphyE is required for the shade avoidance response in the absence of SlphyB1 and SlphyB2.